KUALITAS PELAYANAN DAN KEPUASAN MASYARAKAT PADA PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK (KTP-el) - Yusrizal Yusrizal; Meyzi Heriyanto; Harapan Tua R.F.S (Universitas Riau, 2018)
Service Quality and Community Satisfaction on Electronic Identity Cards (KTPel).This study aims to find out and analyze to service quality in the electronic service (KTP-el) ofthe Department of Population and Civil Registration Kampar District. This study uses aquantitative approach. The sample in this study is Front Office employees using Census Techniquethat is safe 20 employees, while for the Community using Incidental Sampling Technique that is asmany as 30 people. Data analysis using Simple Linear Regression with the help of SPSSapplication. The results showed that service quality was significantly positive for communitysatisfaction with the value of t count (5.720)> t table (2.011). The percentage of supply coefficientis determined as 40.5%. While the remaining 59.5% by other variables not examined such asfacilities and infrastructure, discipline, ability and skills of employees.